SYSTEMATIC LITERATURE REVIEW: INTEGRATION OF BIG DATA AND ARTIFICIAL INTELLIGENCE - Zulfadli, Zulfadli; Syahputra, Ronaldo (Smart Education, 2024)
Abstract: The rapid development of Big Data and artificial intelligence (AI) technology has had a significant impact on various industrial sectors. The integration of these two technologies offers opportunities to improve operational efficiency, innovation, and data-driven decision-making. However, challenges such as privacy, bias, and transparency are still important issues that need to be addressed. This study aims to explore how the synergy between Big Data and AI can be utilized to create added value in various sectors, especially health, finance, and marketing. In addition, this study also aims to identify ethical challenges that arise from the use of these technologies and how these challenges can be managed. The method used in this study involves a comprehensive literature review of previous studies, as well as an analysis of real applications of Big Data and AI in various industries. This study also evaluates the ethical implications of the integration of these technologies by considering aspects of privacy, bias mitigation, and transparency. The results of the study show that the integration of Big Data and AI can significantly improve the decision-making process, product innovation, and operational efficiency in various sectors. In the health sector, for example, AI is able to analyze patient data to personalize care, while in the financial sector, AI helps in risk management and fraud detection. However, the study also emphasizes the importance of managing ethical issues to ensure the responsible use of these technologies. Overall, the synergy between Big Data and AI offers great potential for industrial transformation and improving social outcomes, but requires special attention to ethical and governance aspects.Keywords: artificial intelligence; big data integration; impact analysis. Abstrak: Perkembangan pesat teknologi Big Data dan kecerdasan buatan (AI) yang telah memberikan dampak signifikan pada berbagai sektor industri. Integrasi antara kedua teknologi ini menawarkan peluang untuk meningkatkan efisiensi operasional, inovasi, dan pengambilan keputusan berbasis data. Namun, tantangan seperti privasi, bias, dan transparansi masih menjadi isu penting yang perlu diatasi. Penelitian ini bertujuan untuk mengeksplorasi bagaimana sinergi antara Big Data dan AI dapat dimanfaatkan untuk menciptakan nilai tambah di berbagai sektor, khususnya kesehatan, keuangan, dan pemasaran. Selain itu, penelitian ini juga bertujuan untuk mengidentifikasi tantangan etika yang muncul dari penggunaan teknologi ini dan bagaimana tantangan tersebut dapat dikelola. Metode yang digunakan dalam penelitian ini melibatkan tinjauan literatur yang komprehensif terhadap studi-studi sebelumnya, serta analisis terhadap aplikasi nyata dari Big Data dan AI di berbagai industri. Penelitian ini juga mengevaluasi implikasi etis dari integrasi teknologi ini dengan mempertimbangkan aspek privasi, mitigasi bias, dan transparansi. Hasil penelitian menunjukkan bahwa integrasi Big Data dan AI dapat secara signifikan meningkatkan proses pengambilan keputusan, inovasi produk, dan efisiensi operasional di berbagai sektor. Di sektor kesehatan, misalnya, AI mampu menganalisis data pasien untuk mempersonalisasi perawatan, sementara di sektor keuangan, AI membantu dalam manajemen risiko dan deteksi penipuan. Namun, penelitian ini juga menekankan pentingnya pengelolaan isu-isu etika untuk memastikan penggunaan teknologi ini secara bertanggung jawab. Secara keseluruhan, sinergi antara Big Data dan AI menawarkan potensi besar untuk transformasi industri dan peningkatan hasil sosial, namun memerlukan perhatian khusus pada aspek etika dan tata kelola.Kata kunci: analisis dampak; integrasi big data; kecerdasan buatan.